Extracting three-dimensional (3D) spatial information from sequential oblique unmanned aerial system (UAS) imagery for digital surface modeling - Cheng, Min-Lung; Matsuoka, Masashi (International journal of remote sensing, 2021)
The advent of unmanned aerial system (UAS) has prompted close-range imagery a prevalent source to diversify spatial applications. In addition to nadir scenes, UAS is able to take oblique imagery, which increases the opportunity to acquire sophisticated spatial information from different viewing angles. These images provide more possibilities to reconstruct the land surfaces more completely in three-dimensions (3D). However, dealing with UAS imagery for 3D modelling has been a challenging task for years due to unstable and/or unknown exterior orientation parameters (EOPs) measured by direct georeferencing. With sequential oblique UAS imagery with inadequate or missing EOPs, this paper attempts to extract 3D spatial information from these types of images to achieve digital surface reconstruction. A modular workflow integrating the recovery of camera EOPs and 3D reconstruction in a relative space is presented. These images are spatially related by a feature-based incremental structure-from-motion (fi-SfM) for localization, stereo pairs selection and modification. Digital surface reconstruction, thenceforth, is addressed through dense matching and space intersection upon the outcomes of fi-SfM. The experimental results show that the designed schema is coherent in estimating the camera EOPs and modifying the inappropriate image pairs for improved 3D reconstruction. Furthermore, the surface model generated by discrete stereo pairs can be merged automatically to present a complete digital surface model (DSM). The completeness assessment has verified that the majority of the land surface can be successfully obtained by more than 90%, and the accuracy less than 1 (m) indicates that the implemented workflow can be used to achieve 3D modelling effectively.